Performance assessment of deck link slabs in multi-span bridges: a case study of the Plott Creek Bridge - Villamizar, Sandra; Abdelaleim, Osama; Gomez, Daniel; Ramirez, Julio; Haikal, Ghadir (Frontiers in Built Environment, 2025)
The use of link-slab connections in simply supported multi-span bridge decks is a widely adopted strategy to minimize the number of expansion joints, reducing long-term maintenance issues and improving the roadway surface quality. Current design practice for debonded link slabs primarily focuses on live loads, assuming that the girders behave as simple spans while neglecting the influence of girder support conditions. The link slab is typically considered to be in pure bending and is designed to accommodate girder end rotation. A bond-breaker material is employed between the top of the girders and the bottom of the link slab to reduce the induced stresses and control cracking at the connection region. Within the debonded length, typically set at 5% of each span length, the existing stirrups and shear connectors are removed. Additionally, adequate reinforcement is provided to satisfy crack width control requirements at service limit states. Despite these measures, field observations indicate persistent cracking and leakage issues in link slabs early in their service life. Several investigations suggest that temperature gradients and shrinkage effects are primary contributors to these cracks. Additionally, studies have shown that link slabs experience both axial tension and bending, challenging the assumption of pure bending behavior. The novelty of this study lies in quantifying the effects of thermal gradients within the widely used simplified design framework, thereby providing engineers with practical metrics to adapt the method for improved design accuracy. A numerical evaluation of the response of link slabs is performed using finite element analysis to model the combined effects of traffic loads and vertical temperature gradients. The slabs are analyzed under HL-93 loading and temperature gradients following AASHTO LRFD Bridge Design Specifications. A parametric study is conducted to examine the influence of girder support conditions and debonded length on link slab performance. The computational results highlight the significant role of temperature gradients and girder support conditions in inducing elevated stresses and promoting crack formation at the link slab. The findings presented in this paper emphasize the need to account for these parameters in the design of link slabs to enhance their durability and structural performance. Moreover, the applicability of the simplified rotation-based design approach is reaffirmed, with proposed modifications enabling it to capture the combined effects of live load and thermal gradients.